2002
DOI: 10.1016/s0079-6816(01)00056-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and catalysis on well-defined epitaxial iron-oxide layers

Abstract: Metal-oxide based catalysts are used for many important synthesis reactions in the chemical industry. A better understanding of the catalyst operation can be achieved by studying elemantary reaction steps on well-defined model catalyst systems. For the dehydrogenation of ethylbenzene to styrene in the presence of steam both unpromoted and potassium promoted iron-oxide catalysts are active. Here we review the work done over unpromoted single-crystalline FeO(111), Fe 3 O 4 (111) and α-Fe 2 O 3 (0001) films grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
610
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 579 publications
(670 citation statements)
references
References 324 publications
49
610
2
2
Order By: Relevance
“…In other words, the Pt lattice constant is expanded from 0.277 to 0.297 nm [17]. In principle, this assumption would be consistent with the high adhesion energy between Pt and iron oxide as discussed above.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In other words, the Pt lattice constant is expanded from 0.277 to 0.297 nm [17]. In principle, this assumption would be consistent with the high adhesion energy between Pt and iron oxide as discussed above.…”
Section: Resultssupporting
confidence: 68%
“…The termination of the close-packed surfaces of iron oxides has been addressed by Weiss and Ranke in their review [17]. In particular, it has been suggested that the Fe 3 O 4 (111) surface is terminated by ¼ monolayer of Fe cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All spectra can be fitted using Eqs. (1)(2)(3) with three discrete resonant modes having resonant frequencies ( q  ) at 3365, 3520, and 3670 cm - We consider first the three models of -Al 2 O 3 (1102 ) described in the introduction section. The ideal bulkterminated model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37] Here, we present only the key points needed for data analysis. The SF signal generated by overlapping incoming beams of frequencies  vis and  ir at a surface in the reflected direction is given by 3  at the interface. The surface nonlinear susceptibility (2)   can be approximated by (2) …”
Section: Theoretical Backgroundmentioning
confidence: 99%